2012
DOI: 10.1021/mz300391g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long Range Interactions on the Glass Transition Temperature of Thin Polystyrene Films

Abstract: The glass transition temperature (T g) of thin polystyrene (PS) films supported on silicon wafers with oxide layers of varying thickness was characterized by the temperature dependence of the film thickness using ellipsometry. This allowed us to uncover how a long-range interaction affects the T g of polymer films. As previously reported using a variety of methods, the T g decreased with decreasing film thickness. However, the extent was not the same among the reports. In this study, we found that the T g atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 52 publications
4
44
0
Order By: Relevance
“…However, within experimental accuracy, this value was the same as that for PS-H at 392 K. In addition, the T g for the 20-nm-thick film on silicon was determined by examining its thickness as a function of temperature via ellipsometry. 44 The values obtained for PS-H and PS-N were again identical (Supplementary Figure S2). Thus, it can be concluded that the segmental mobility in the interfacial region, at least within this depth range, was not restricted by the introduction of the functional end group.…”
Section: Interfacial Chain Mobilitysupporting
confidence: 55%
“…However, within experimental accuracy, this value was the same as that for PS-H at 392 K. In addition, the T g for the 20-nm-thick film on silicon was determined by examining its thickness as a function of temperature via ellipsometry. 44 The values obtained for PS-H and PS-N were again identical (Supplementary Figure S2). Thus, it can be concluded that the segmental mobility in the interfacial region, at least within this depth range, was not restricted by the introduction of the functional end group.…”
Section: Interfacial Chain Mobilitysupporting
confidence: 55%
“…61,93 The stronger attractive interaction between PS and H-Si is also supported by solvent leaching experiments of the supported PS film with toluene, which show that the thickness of the residual PS layer on H-Si is higher than that on SiO x -Si. It has been shown that hydrogen-terminated Si is more strongly adsorbed by PS than SiO x , 61,93 due to higher thermodynamic work of adhesion 57 and the positive interfacial potential.…”
Section: Investigation Of the Rheological Behavior Of Supported Thin mentioning
confidence: 76%
“…For example, it is well established that for supported films of linear polymer chains, T g decreases as a function of decreasing thickness in cases where there is little or no interaction between polymer and substrate, e.g., polystyrene (PS) films supported on Si/SiO x . 7,[10][11][12]16,17,34 In contrast, an increase in T g with confinement is observed in systems with sufficiently large attractive polymer-substrate interactions, e.g., poly(methyl methacrylate) (PMMA) films supported on Si/SiO x . 8,13,19 Any attempt to draw comparisons between the effects of different substrates on DSC-determined T g -confinement behavior in supported, ultrathin polymer films would be exceedingly complex.…”
Section: Introductionmentioning
confidence: 99%